Hagyományos magyar élelmiszerek: valódi lehetőségek a kisvállalkozások számára? - Polereczki, Zsolt; Szente, Viktória; Szigeti, Orsolya; Szakály, Zoltán (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
It is getting a more and more important question that where are the break trough points for the small and medium sized enterprises (SMEs) working in the food industry because of the strengthening market share of the import food products. We compare the SMEs marketing abilities to the consumer demands on high value added traditional Hungarian dishes to examine their possibilities to take the opportunity of these niche markets. The examination aims to clarify two core questions. On the one hand whether the SMEs are able to perceive the consumers’ behaviour on these markets? On the other hand is the production of these products a real option for them? The research reveals that the enterprises have significant deficiencies in the field of marketing therefore most of them have limited opportunity to get to know the consumers and reach them effectively.